Manejo de la exacerbación aguda en la enfermedad pulmonar obstructiva crónica - Gayoso Cervantes, Oscar (2009)
Chronic obstructive lung disease (COPD) is an important cause of death in industrialized countries (it is the 4th cause of death in the U.S.). This condition is also prevalent in developing countries, in some its frequency may be higher, and it is an important cause of hospitalizations and consultations because of acute exacerbations. The Anthonisen definition is the most widely and accepted instrument for diagnosing COPD exacerbations, pointing out at the presence of one or more of the following: increased sputum volume, change of color of the sputum, and worsening dyspnea. Patients with COPD may develop one to three acute exacerbation episodes per year. The number of these episodes is an important marker for the severity of COPD, since it determines quality of life and the mortality risk. Three to sixteen per cent of affected patients may require hospitalization (this rate may be higher in more severe cases). In-hospital mortality may reach 10% in severe COPD cases, and it becomes increased if the patient is admitted to an intensive care unit. The etiology of acute exacerbations of COPD is mainly because of infections (up to 80%), but other conditions may also account for such exacerbations, such as pulmonary embolism, pneumothorax, heart failure, thoracic trauma (including rib fracture), and extrapulmonary infections, being considered as triggering factors, and they may also coexist. Differently from asthma crisis, it is important to have a chest X-ray film taken and arterial blood gases determinations in every patient presenting to the emergency department with an acute exacerbation of COPD. Up to 20% of patients may present with elevated PCO2. When administering oxygen, it is preferable to use a Venturi mask with an oxygen concentration able to maintain hemoglobin saturation around 90% (86-92%). The first choice therapy in these cases is the use of a bronchodilator agent. The best option is to use a short acting beta-agonist or an anticholinergic drug, and these drugs may be combined if the patient does not improve his/her condition. The choice of drugs to be use will depend on the underlying conditions of the patient and on the potential side effects. Nebulizations are quite useful, and the use of fixed-dose pressurized inhalers is not precluded; in case of using these devices, a spacer must be used. The use of systemic steroids is controversial. These compounds must not be used for long time periods. If used, therapy should not last for more than 14 days. Antimicrobials are quite useful. Generally speaking, microorganisms involved include enteric Gram-negative bacteria, which are more drug-resistant as long as the obstruction becomes worse (lower FEV1 values) with a worsening clinical condition. It is important to rule out the presence of active tuberculosis, especially if fluoroquinolone compound active against M. tuberculosis are to be used. The choice for antibacterial therapy will depend on the severity of the condition as well as on the presence of risk factors for the development of resistance to antimicrobial agents. Physiotherapy and mucolytic agents have a limited role in an acute setting, but they are important when dealing with COPD management in the long term. A great breakthrough in the management of acute exacerbations of COPD is non-invasive ventilation, which is a safe and effective approach for treating patients with acute hypercarbia. Non-invasive ventilation may fail in up to 30% of all cases, depending on the degree of academia and CO2 levels on admission. Non-invasive ventilation allows the diaphragm muscle to relax and overcome the critical situation preventing exhaustion. Non-invasive ventilation has been proven to reduce the number of intubations and mortality in patients with acute exacerbations of COPD.